Cytotoxic Diterpenoids from the Roots of Aralia melanocarpa - Jiang, Zhi-Yong; Yang, Chun-Tao; Hou, Shu-Qun; Tian, Kai; Wang, Wei; Hu, Qiu-Fen; Huang, Xiang-Zhong (Planta Medica, 2016)
Five new diterpenoids (1–5) were isolated from the roots of Aralia melanocarpa, together with four known compounds, 7β-hydroxy-ent-pimara-8(14),15-diene-19-oic acid (6), 18-norpimara-8(14),15-dien-4-ol (7), ent-16βH,17-isovalerate-kauran-19-oic acid (8), and ent-16α,17-dihydroxykauran-19-oic acid (9). Based on the MS, IR, and NMR spectral analysis, the structures of the five new diterpenoids (1–5) were elucidated. The cytotoxic activities of compounds 1–9 were assayed, and compounds 1 and 2 showed cytotoxicity in four cancer cell lines with IC50s from 4.2 to 8.2 µM.
Keywords: Aralia melanocarpa; Araliaceae; ent-pimarane; diterpenoid; cytotoxicity